Telomere length diversity under the influence of heat and feed restriction stresses in broiler chicken Gallus gallus domesticus - Badmus, K. A.; Zulkifli, Idrus; Meng, G. Y.; Farjam, Abdoreza Soleimani; K., Mamat-Hamidi (Verlag Eugen Ulmer, 2022)
This work was designed to evaluate telomere length attrition as biomarker of stress in meat type chickens exposed to acute stresses. Forty male broilers (20 birds in each treatment group and 20 in the respective control group) of equal weight (1700 ± 100 g) each were selected at 35 days of age from three hundred Cobb500TM broilers for a heat stress (HS) and a feed restriction (FR) group, respectively. The HS-group was exposed to 34°C for 6 hours per day while the FR-group was exposed to 60% feed reduction per day. Collection of blood samples, measurements of growth performances and evaluation of telomere length were conducted at the end of week 6 and 7. Significant interaction (P < 0.05, DF = 39) between age and FR on body weight of the chicken was noticed. Effect of FR was noted for body weight (P < 0.0001, DF = 39), body girth (P < 0.0001, DF = 39) and drumstick length (P < 0.018, DF = 39). Significant effect of HS was found for body weight (P < 0.0001, DF = 33) and body conformation traits. Significant effects of FR and HS (P < 0.05, DF = 46) were observed on the telomere length. Telomere length was significantly (P < 0.05) higher in the FR chicken kept in the open sided house type than the HS counterpart kept in the close chamber at week 7. Our result revealed that telomere length has a medium (r = 0.52, P < 0.05) and positive correlation with body weight at week 6. Therefore, it is concluded that telomere length could be used as an important physiological stress biomarker in meat type chickens and for selecting traits of economic importance.